Ribosomes containing mutants of L4 ribosomal protein from Thermus thermophilus display multiple defects in ribosomal functions and sensitivity against erythromycin - TSAGKALIA, AIKATERINI (Copyright 2005 by RNA Society, 2005)
Protein L4 from Thermus thermophilus (TthL4) was heterologously overproduced in Escherichia coli cells. To study the implication of the extended loop of TthL4 in the exit-tunnel and peptidyltransferase functions, the highly conserved E56 was replaced by D or Q, while the semiconserved G55 was changed to E or S. Moreover, the sequence -G55E56- was inverted to -E55G56-. When we incorporated these mutants into E. coli ribosomes and investigated their impact on poly(Phe) synthesis, high variations in the synthetic activity and response to erythromycin of the resulting ribosomes were observed. In the absence of erythromycin, ribosomes harboring mutations G55E and E56D in TthL4 protein were characterized by low activity in synthesizing poly(Phe) and decreased capability in binding tRNA at the A site. On the other hand, ribosomes possessing mutations G55E, G55S, G55E-E56G, or E56Q in TthL4 protein were unexpectedly more sensitive to erythromycin. Evidence in support of these findings was drawn by in vivo experiments, assessing the erythromycin sensitivity of E. coli cells expressing wild-type or mutant TthL4 proteins. Our results emphasize the role of the extended loop of L4 ribosomal protein in the exit-tunnel and peptidyltransferase center functions.